Urbanização e impactos sobre áreas de preservação permanente : o caso do Rio Jucu-ES - Holz, Ingrid Herzog (2012)
It analyzes the urban river spaces, addressing the impacts of urbanization, the importance of these impacts in the cities and the current possibilities for preservation and restoration. Jucu River is used as an empirical context, one important watershed i